2022
DOI: 10.7759/cureus.22476
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Weakness, Opportunities, and Threats (SWOT) Analysis of Virtual Outpatient Department Under Telemedicine Department During the COVID-19 Pandemic

Abstract: BackgroundCOVID-19 pandemic has challenged all current management tools used for patient care. This study aims to determine strength, weakness, opportunities and threats (SWOT) to virtual OPD and consultants' perceptions of teleconsultation virtual OPD during the COVID-19 pandemic, adapting to newer technologies for successfully handling this situation. Material and methodsA facility-based cross-sectional study was conducted at the Virtual OPD of All India Institute of Medical Sciences Rishikesh among patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Medicine, Obstetrics, Gynecology, Pediatrics, and Dermatology queries are mainly addressed by TM services 27 . Another study demonstrated that TM was mostly used for Radiotherapy, General Medicine, and Cardiology-associated consultations 34 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicine, Obstetrics, Gynecology, Pediatrics, and Dermatology queries are mainly addressed by TM services 27 . Another study demonstrated that TM was mostly used for Radiotherapy, General Medicine, and Cardiology-associated consultations 34 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…TM plays a positive role in improving patients’ outcomes seeking care for cardiovascular diseases, endocrinology, dermatology, psychiatry, nephrology, neurology, ophthalmology, and respiratory ailments 57 or primary healthcare (44.5%) consultations 27 , 58 . Queries related to radiotherapy and chemotherapy are common 44 . People with multiple diseases, young adults, and males sought TM services more 34 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some domestic scholars have built a prediction model of SWOT audience online conversion rate by Shimizu K. [ 4 ] to analyze the audience online conversion rate. The results show that SWOT has a high analysis effect on each index of audience conversion rate Saxena V. [ 5 ].…”
Section: Introductionmentioning
confidence: 99%